VIGENERE CIPHER DENGAN MODIFIKASI PLAINTEXT - Gusti, Dwi Rahmasari Kinasih; Santoso, Kiswara Agung; Kamsyakawuni, Ahmad (Jurusan Matematika FMIPA Universitas Jember, 2020)
Cryptography is knowledge of encoding messages by observe to security aspects. Cryptography uses two types of keys, namely symmetric keys and asymmetric keys. Vigenere cipher is a technique to encrypt messages by symmetric key. Vigenere cipher can be combined by several patterns and ASCII code. The pattern used can vary as long as the text can be returned to original message (can be decrypted). On this paper, we will modified plaintext before encrypt using vigenere cipher. The way to modified the plaintext are flip and shift rows of bit. The effect of the algorithm changes can be seen based on the renewal value obtained. If the correlation value gets smaller, it means the algorithm is better. The results of this study is the correlation value using vigenere cipher with modified plaintext is better compared to vigenere cipher with original plaintext. Keywords: ASCII, Patterned, Bits, Vigenere Cipher